DIGITAL TRANSFORMATION IN HEALTHCARE EDUCATION: PREPARING MEDICAL MANAGERS FOR THE FUTURE - Олексій Наливайко; Олексій Бачук (Відкрите освітнє е-середовище сучасного університету)
The article addresses the integration of digital tools in the training of medical managers,